Females suffer a reduction in the viability of stored sperm following an immune challenge. (20th November 2013) - McNamara, K. B.; van, E.; Simmons, L. W.
Abstract Despite the ubiquitous nature of sperm storage in invertebrates, relatively little is known about its costs, or the impact that immune activation can have on a female's ability to maintain viable sperm stores. We explored the effects of an immune challenge on sperm storage under food‐limited and ad libitum conditions in the field cricket, Teleogryllus oceanicus, by injecting mated adult females with either a LD5 dose of live bacteria or a nonpathogenic immune elicitor [lipopolysaccharide (LPS)] and then scoring the viability of their stored sperm. Females that were infected with bacteria showed a reduction in the viability of stored sperm 48 h after infection; interestingly, this pattern was not evident when females were injected with LPS. Reduction in sperm viability post‐infection may reflect a reproductive trade‐off between immune function and sperm store maintenance, as only females injected with bacteria showed an elevated antibacterial immune (lytic) response. Alternatively, bacteria may act directly on sperm quality. Dietary manipulations showed that lytic activity in females is condition dependent, irrespective of their immune challenge treatment. Diet affected the ability of females to maintain the viability of stored sperm, suggesting that sperm storage is condition dependent. That bacterial infection associated with a reduction in stored sperm quality has potentially important implications for the outcomes of sperm competition in T. oceanicus and in other species in which females store sperm between matings.